A Study and Implementation of a Template-Based Online Advertisements Management System (AMS) for INTI University Education Purpose - Chin, Yun Onn (2010)
This project studies the importance of online advertisement and implementation a platform for INTI University to advertise all necessary advertisements and events. The project futher develop by categorize the advertisements into category and different type manage each kind of advertisement from different sources. The purpose of the project is to allow the students and staff of INTI University can have a platform to share their advertisements and reach the purpose of advertising. Nest this particular platform allows the users can share their advertisement’s templates which mainly are pictures for designing purpose. The main function that the website will perform is the management of the advertisements which will sort out the advertisement automatically accordingly to date and time of uploading . Other than that, the website allow the users to upload their template and allow to share with others which means others users are possible to download the template from the website for their own purpose which mainly is designing purpose. Next the website will sort the advertisement base on the date and remove the outdated advertisement so that it is always updated. Following on , there will be a list of suggestion title of advertisement suggest to the user based on their user type which suit them most. The main target users of this particular project are obviously for the students and the staff of the University to encourage them to advertise their events and get information from there too. The admin of the system will have to approve the advertisements content after the system verifies the user type to avoid spam and improper advertising. Other than that, the parents of the students who wish know more about this University through this website by more interacting and more details information other than hard copy and brochure. In conclude, this project will help the users to reduce their time and effort of finding information and advertising events and create a platform to increase the interaction between staff, students and the public.